Q&A - Ask Doubts and Get Answers
Q

By using properties of determinants, show that: determinant x+y+2z x y z y+z+2x y z x z+x+2y =2(x+y+z)^3

Q : 11        By using properties of determinants, show that:

                  (ii) \begin{vmatrix} x+y+2z &x &y \\ z & y+z+2x & y\\ z & x &z+x+2y \end{vmatrix}=2(x+y+z)^3

Answers (1)
Views

Given determinant

  \triangle =\begin{vmatrix} x+y+2z &x &y \\ z & y+z+2x & y\\ z & x &z+x+2y \end{vmatrix}

Applying C_{1} \rightarrow C_{1}+C_{2}+C_{3}   we get;

=\begin{vmatrix} 2(x+y+z) &x &y \\ 2(z+y+x) & y+z+2x & y\\ 2(z+y+x) & x &z+x+2y \end{vmatrix}

Taking 2(x+y+z) factor out, we get;

=2(x+y+z)\begin{vmatrix} 1 &x &y \\ 1 & y+z+2x & y\\ 1 & x &z+x+2y \end{vmatrix}

Now, applying row transformations, R_{1} \rightarrow R_{1} -R_{2}  and then R_{2} \rightarrow R_{2} -R_{3}.

we get;

=2(x+y+z)\begin{vmatrix} 0 &-x-y-z &0 \\ 0 & y+z+x & -y-z-x\\ 1 & x &z+x+2y \end{vmatrix}

=2(x+y+z)^3\begin{vmatrix} 0 &-1 &0 \\ 0 & 1 & -1\\ 1 & x &z+x+2y \end{vmatrix}

=2(x+y+z)^3\begin{vmatrix} -1 &0 \\ 1& -1 \end{vmatrix} = 2(x+y+z)^3

Hence proved.

Exams
Articles
Questions